The Role of Filipino Early Career Ocean Professionals (ECOPs): Challenges and Opportunities in the Philippine Domestic Shipping Decarbonization - Reyes, Emerson Madlangbayan (Future Science / FSH-PH Publications, 2025)
The global shipping sector faces strong decarbonization targets, requiring major emission cuts by 2030, 2040, and net zero by 2050. In the Philippines, domestic shipping is vital for connectivity, making this challenge urgent. This study explored Filipino ECOPs’ roles, awareness, challenges, and opportunities in advancing maritime decarbonization policies and practices. A mixed-methods design was employed, combining survey responses from ECOPs, semi-structured interviews with participants, and document analysis of national and international maritime policies. Quantitative analysis assessed awareness and readiness levels, while qualitative insights revealed systemic challenges and enabling conditions. The findings revealed that ECOPs demonstrate moderate to high awareness of environmental aspects of decarbonization (68.6%), yet significant gaps persist in regulatory knowledge, economic understanding, and technical applications (48%). Opportunities for ECOPs’ engagement were rated as “moderate potential” (WM = 3.22), with enabling factors deemed “sufficient” (WM = 2.85). Respondents recognized ECOPs’ capacity to drive technological adoption and policy innovation, though barriers, including restricted access to decision-making, inadequate training, and limited mentorship, pose “major challenges” (WM = 3.15). Policy analysis affirmed national alignment but underscored weak mechanisms for meaningful ECOP participation. ECOP integration is vital to strengthening the Philippines’ maritime decarbonization agenda. Strategic measures such as advisory councils, capacity-building programs, and curriculum reforms are recommended to empower ECOPs for of sustainable shipping transitions in archipelagic contexts.